2015
DOI: 10.3402/gha.v8.27256
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of 5S management method for lean healthcare at a health center in Senegal: a qualitative study of staff perception

Abstract: Background5S is a lean method for workplace organization; it is an abbreviation representing five Japanese words that can be translated as sort, set in order, shine, standardize, and sustain. The 5S management method has been recognized recently as a potential solution for improving the quality of government healthcare services in low- and middle-income countries.ObjectiveTo assess how the 5S management method creates changes in the workplace and in the process and outcomes of healthcare services, and how it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 16 publications
5
66
0
6
Order By: Relevance
“…To the best of our knowledge, this is the first quasi-experimental study that showed the impact of 5S in healthcare settings (18). Apart from the qualitative study conducted at the Tambacounda Health Center (17), no other study has highlighted the impact of 5S at resource-poor health facilities in LMICs. Second, the present study's results provided certain ideas about how the 5S intervention led to the increase in client satisfaction scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first quasi-experimental study that showed the impact of 5S in healthcare settings (18). Apart from the qualitative study conducted at the Tambacounda Health Center (17), no other study has highlighted the impact of 5S at resource-poor health facilities in LMICs. Second, the present study's results provided certain ideas about how the 5S intervention led to the increase in client satisfaction scores.…”
Section: Discussionmentioning
confidence: 99%
“…In Senegal, government health facilities experienced chronic problems related to human resources for health and pharmaceutical supplies (30). Additionally, in the qualitative study conducted at the Tambacounda Health Center, most of the health workers reported poor physical and material resources as obstacles to improving the quality of services (17). It is reasonable to assume that these resource problems were present at all of the health centers in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Entre os estudos mais comuns da metodologia é possível encontrar na literatura um framework geral para implementação do Lean em instituições de saúde é implementado (Yu et al, 2015), Benchmarking de melhores práticas (Narayanamurthy & Gurumurthy 2016), estudo de tempos e movimentos (Fisher et al, 2016), e 5S (Kanamori et al, 2015).…”
Section: Esperasunclassified